Identification of Bacterial Genes Expressed During Diatom-Bacteria Interactions Using an in Vivo Expression Technology Approach - Torres-Monroy, Ingrid; Ullrich, Matthias S. (Frontiers in Marine Science, 2018)
Diverse microalgae-bacteria interactions play important roles for nutrient exchange processes and marine aggregate formation leading to the cycling, mineralization, or sedimentation of organic carbon in the Oceans. The main goal of this study is to report an alternative way to assess a distinct diatom-bacteria interaction. To study this at the cellular scale, an in vitro interaction model system consisting of the diatom, Thalassiosira weissflogii, and the gamma-proteobacterium, Marinobacter adhaerens HP15, had previously been established. HP15 is able to attach to T. weissflogii cells, to induce transparent exopolymeric particle formation, and to increase marine aggregation formation. Several bacterial genes important during this interaction have been studied thus far, but genes specifically expressed in co-culture remained unknown. To identify such bacterial genes, an in vivo Expression Technology (IVET) screen was employed. For this, a promoter-trapping vector containing a fusion between a promoter-less selection marker gene and a promoterless reporter gene was constructed. Construction of a library of plasmids carrying genomic fragments upstream of the fusion and its subsequent transformation into a selection marker mutant allowed detection of 30 bacterial promoters specifically expressed during the interactions with T. weissflogii. Their sequence analyses revealed that the corresponding genes could be involved in many processes such as biochemical detection of diatom cells, bacterial attachment, metabolic exchange of nitrogen compounds, and resistance toward heavy metals. Identification of genes potentially involved in branched-chain amino acid uptake and utilization confirmed our previous results of a proteomics analysis. Since our current approach identified several additional genes to be induced in co-culture, use of IVET might be a valuable complementing strategy to proteomic or transcriptomic analysis of the diatom-bacteria crossplay. The current IVET approach demonstrated that the interaction between M. adhaerens HP15 and T. weissflogii is multifactorial and is likely to involve a complex network of physiological processes.